(3TQM GdeUWcGhj Ydi GdebOeI GdLRQjIs - (3eMehO Hf YeQ Hf Ydj GdTgjQ HGdeUWcGhj GdNGfcjs
(3ChdgG (B:s
(3CeG HYO jbhd GdYHO GdWGeY aj Uah YahGddgGdTgjQ HGdeUWcGhj Efj eeG EHJOCJ HMaXg hJMUjdg s
(3BNQgG (B:s
(3eY Efj cPdc Ydi LfGM GdZQHI hgPG BNQ eG JSgd LYdg Gddg NGdUkG dhLgg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B292 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B188s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1799s
Keywords: (3GdbQGAGJ hGdJLhjOs